WACANA KEKERASAN SIMBOLIK PADA CERITA WANDIUDIU - Jafar Karim (Program Magister Linguistik Universitas Udayana, 2015)
This study focused on the symbolic violence discourse in Wandiudiu folklore from Lakudo Buton district of Southeast Celebes. The story was selected due to its familiar and grounded in local communities in the area. Research approach is based on text and context. In which the approach focused on literary work and based many aspects such as history, culture, and religion. The living values in the society would be attributed with social construction of the story.The study used descriptive qualitative method which uncovered facts, circumstances, and phenomenon. The study as well intepreted data related to given situation, the view points of society, conflicts, the difference between facts, and the influence of particular problem which was studied and investigated. The data was obtained from oral literature which was shared by the native speakers. In addition, the research also applied observation. Data source is either Wandiudiu folklore in Buton native language, or transliterated from a number of informants in the area. Based on the analysis, the study found some forms of symbolic power discourse included, complience, and dicipline.